No business is an island : making sense of the interactive business world - Håkansson, Håkan, 1947-; Snehota, Ivan (Emerald Publishing Limited, 2017)
The interactive dimension is crucial for the development and growth companies and of the economy. In management, creating and appropriating value depends on relating your business to other businesses. When developing strategy, innovating, marketing, purchasing or accounting there is the need to handle the local specific interdependencies in business relationships that characterize the interactive world. That implies a conception of the task and priorities of management and the critical managerial skills that is only partly acknowledged in the contemporary management theory. This book provides empirical insights into the often hidden interactive aspects of the contemporary business world. It offers a novel perspective and theoretical and methodological tools for analysis of interactive aspects related to topics such as management, strategy, purchasing, marketing and accounting as well as issues related to economic and regional policies including public purchasing and the role of ownership.- Resumé vydavatel
Obsahuje index.
Keywords: podnikatelské sítě; strategické aliance; obchodní komunikace; business networks; strategic alliances (business); communication in business; sborníky; elektronické knihy; papers of several authors; electronic books